Eksplorasi Kreativitas Pedagogik Mahasiswa STKIP Biak dalam Penggunaan Aplikasi Capcut sebagai Pemenuhan UAS - Nasri Indra Padang; Syutri Bawan Rumondor; Suzana Agusta Maria Weyai (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study analyzes the pedagogical creativity of STKIP Biak students in using the CapCut application to complete their final semester examinations (UAS). The study involved six subjects. Both primary and secondary data were utilized. Data collection techniques included non-participant observation, semi-structured interviews, and a review of relevant literature. Data analysis involved data reduction, data presentation, and conclusion drawing. Methodological triangulation was employed to ensure data validity. The results indicate that (1) the forms of pedagogical creativity demonstrated by STKIP Biak students in creating videos with CapCut include: (a) creativity in media usage, such as varied camera angles and audio tailored to the theme; (b) creativity in structuring the lesson flow—covering the opening, core content, and closing; (c) creativity in enhancing video appeal through relevant content and sharp, natural visual quality; and (d) alignment of the video with learning objectives. (2) Factors supporting and hindering STKIP Biak students in using CapCut for their final exams include: (a) ease of application use and the availability of functional templates; (b) experience with editing software, fostering feelings of pride and satisfaction; and (c) limitations regarding access and storage capacity. (3) The students' experience in effectively and efficiently integrating learning materials into the videos they created. (4) Student perceptions regarding the use of CapCut as a tool to support final exam completion, examined through: (a) the impact of creativity on self-confidence, where practical features encourage students to be open about their skills.